2014
DOI: 10.1111/add.12589
|View full text |Cite
|
Sign up to set email alerts
|

Prize-based contingency management for the treatment of substance abusers: a meta-analysis

Abstract: Aim To review randomized controlled trials to assess efficacy of a prize-based contingency management procedure in reducing substance use (where a drug-free breath or urine sample provides a chance of winning a prize). Methods A meta-analysis was conducted on articles published from January 2000 to February 2013 to determine the effect size of studies comparing prize-based contingency management to a treatment-as-usual control condition (k=19 studies). Parallel analyses evaluated the efficacy of both short- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
163
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(170 citation statements)
references
References 67 publications
(115 reference statements)
5
163
0
2
Order By: Relevance
“…positive reinforcer, it competes with the reinforcing effects of the drug and increases the likelihood that drug abstinence is initiated and maintained [30].The reason this seems to be effective is that the benefits typically outweighs the benefits of using the drug. Therefore, this method could be utilized in sessions while utilizing the harm reduction approach.…”
Section: Journal Of Drug Abuse 2471-853xmentioning
confidence: 99%
“…positive reinforcer, it competes with the reinforcing effects of the drug and increases the likelihood that drug abstinence is initiated and maintained [30].The reason this seems to be effective is that the benefits typically outweighs the benefits of using the drug. Therefore, this method could be utilized in sessions while utilizing the harm reduction approach.…”
Section: Journal Of Drug Abuse 2471-853xmentioning
confidence: 99%
“…BT was, in part, a reaction to psychoanalysis that was seen as pessimistic, deterministic, and nearly impossible to investigate empirically. An example of a behavioral approach to substance abuse therapeutics is contingency management (CM [55,56]). CM uses the principles of operant conditioning and provides established reinforcers for drug abstinence or other objective measures of drug abstinence.…”
Section: Cognitive Behavior Therapymentioning
confidence: 99%
“…[89] Review of the effectiveness of mindfulness interventions with substance use disorders [55] Evaluation of a contingency management program to reduce substance use Substance Abuse Therapeutics http://dx.doi.org/10.5772/64264…”
Section: References Notesmentioning
confidence: 99%
“…A number of meta-analyses 4 have shown that incentives work considerably better than more conventional addiction-management programmes, particularly when vouchers are added to the protocol. What is more, says Higgins, vouchers are the only treatment so far that works for cocaine users.…”
Section: Offshoot Of the Cocaine Epidemicmentioning
confidence: 99%